Compound Verb Formation in Modern Uzbek Language - Dilnoza Nashirova (Genius Journals, 2022)
Word formation means the formation of a new word in current linguistics. Word formation in relation to derivation is considered as the formation of a new word in Uzbek linguistics, which is both the formation of a word and the emergence of a new lexeme on the basis of internal possibility of a word-formation pattern. This article provides an overview on compound verb formation in Modern Uzbek language
Keywords: Compound verb; auxiliary verb; case; noun